Leguminosae invasive species in cultures in the northeast of Pará, Brazil - Silva, Mônica Falcão da; Gurgel, Ely Simone Cajueiro; Souza Filho, Antonio Pedro da Silva; do Carmo, Maria de Nazaré Lima (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2013)
Invasive plants are any plants find in places where their presence is not desired for causing numerous direct and indirect effects on agricultural activities of man, but they may have important ecological functions. Taxonomic works with invasive Leguminosae in the Amazon are rare and the lack of literature difficult to identify these plants. The work aims to provide an identification key to the invasive species of Leguminosae of cultures, in Terra Alta and the metropolitan region of Belém, northeast of Pará, Brazil, for which all species were collected in areas. During the collections, ten species and eight genera were found. Mimosa L. and Stylosanthes Sw. were the most representative genera of them, each one with two species. Regarding the growth habit, most species were herb to subshrub (3 spp.) and only one tree species (Senna reticulata (Willd.) H.S. Irwin & Barneby) was recorded in the studied areas. In relation to life cycle, most taxa are perennial, and the collected species reproduce mainly by seeds. Descriptions, comments, illustrations and common names of the recorded species are also provided.
Keywords: Mimosa; Stylosanthes; Amazon; Weeds